Countering Zeitgeist of Self-Centered through Role Playing Methods among Junior High School Students - Sandy Ariawan (IJECA (International Journal of Education and Curriculum Application), 2019)
This study aimed to examine the influence of role playing methods on the cognitive, affective, and psychomotor aspects of students in Christian education subjects, as an effort to counter zeitgeist of self-centered. Role playing method can give a strong and durable sense of learning in the students' memories, be a fun learning experience that is difficult to forget, make the classroom atmosphere more dynamic and enthusiastic, arouse passion and spirit in students and foster togetherness, allow students to plunge into the role of something that will be discussed in the learning process. This study is a quantitative research, with simple linier regression. Respondents are students of Public Junior High School 1 Wagir. From field trials and data processing that role playing implementation models have an impact of 34.8% while 65.2% are influenced by other factors. It is recommended role playing method as one of the appropriate method and practices in Christian education.